Evaluation Of The Implementation Of Continuity Of Care Towards The Reduction Of Complications In Postpartum Mothers - Paulina Fonseca de Carvalho; Farida Kartini; Asri Hidayat (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: Postpartum maternal complications remain a significant public health concern, particularly in developing countries. The Continuity of Care (CoC) model is a comprehensive midwifery care approach that provides continuous services from pregnancy through childbirth and the postpartum period and has been suggested as a strategy to improve maternal health outcomes. Objective: This scoping review aimed to map and evaluate the evidence regarding the implementation of Continuity of Care in reducing postpartum maternal complications and to identify factors influencing its implementation. Method: This scoping review followed the Arksey and O’Malley framework enhanced by the Joanna Briggs Institute (JBI) methodology. Literature searches were conducted across several electronic databases using predefined keywords and Boolean operators. Studies were selected based on established inclusion and exclusion criteria. Data were extracted using a standardized form, and methodological quality was assessed using the JBI Critical Appraisal Tools. Reporting followed the PRISMA-ScR guidelines. Result: Eight studies met the inclusion criteria. Six studies reported a reduction in postpartum complications or improved postpartum health outcomes among women receiving CoC services, while five studies found increased maternal satisfaction and better utilization of postpartum care services. Four studies identified continuity and competency of healthcare providers as key facilitators of successful implementation. Additional enabling factors included effective communication, adequate resources, and supportive health policies. Common barriers reported across the studies were workforce shortages, high workloads, and inconsistent policy implementation. Conclusion: The available evidence suggests that Continuity of Care may contribute to improved postpartum outcomes and maternal satisfaction. However, variations in study design and implementation contexts limit definitive conclusions regarding its effectiveness. Strengthening healthcare workforce capacity, ensuring adequate resources, and enhancing policy support may facilitate more effective implementation of Continuity of Care, particularly in developing countries.